Successful Endoscopic Management of a Renal Fungal Ball using Flexible Ureterorenoscopy. (24th December 2019) - Abuelnaga, Mahmoud; Khoshzaban, Sadegh; Reda Badr, Mahmoud; Chaudry, Aasem
Abstract : Background . Candida as a cause for urinary tract infection in healthy individuals is unusual. The extension of fungi into the urinary collecting system rarely leads to formation of bezoars or fungus balls. This can in turn lead to hydronephrosis, obstructive uropathy and sepsis. Case Presentation . An eighty years old gentleman presented to A&E with confusion, severe urosepsis and acute kidney injury. CTKUB demonstrated significant right sided hydronephrosis, perinephric fat stranding and gas in collecting system. A year prior to this admission he has become known to the urology team for a fungal ball that was noted in the upper pole of the right kidney which was picked up following elective flexible ureterorenoscopy for right kidney stones. Flexible ureterorenoscopy and successful retrieval of fungal ball by basket was performed. Conclusion . We advocate this technique to be considered as an alternative to the current treatment offered to patients with fungal ball infections and especially so in cases were a nephrostomy is either contraindicated, unavailable, or not possible.